STUDI KASUS : PROGRAM FISIOTERAPI PADA KASUS JUMPERS KNEE DENGAN INTERVENSI ULTRASOUND DAN TERAPI LATIHAN - Dwi Panulat, Pandu; Rizki Prabaningtyas, Ayu; Dien Nurlaila, Ike (Yayasan Putra Sukamanah Sejahtera, 2025)
Jumper's knee is inflammation or irritation of the patellar tendon. Studies case This aim For know influence intervention ultrasound and therapeutic physiotherapy exercise on patients female , 27 years old , with left jumpers knee condition . Method : Study Case done 6 times for 2 weeks with evaluate painful using the Numeric Rating Scale (NRS), Range of motion joints (LGS) with goneometer , Strength muscle with Manual Muscle Testing (MMT), Atrophy muscle with Midline and functional limbs lower with Lower Extremity Functional Scale (LEFS) questionnaire . Result: Yes decline painful Dian, press and move from NRS at the start therapy Silent pain 2, pain press 8, pain movement 6 and in therapy 6th obtained results silent pain 0, pain press 3 and pain motion 2, occurs increase in active ROM in extension movements – flexi dextra (S) 0°-0°-110° from beginning therapy becomes (S) 0°-0°-145° at the end therapy , happens enhancement strength muscle In Therapy 1 it was obtained results in extension 3 and flexion 3- movements in therapy 6th obtained results in extension 4 and flexion 3 movements , there are enhancement mass muscles in Therapy 1 were obtained results 10 cm superior patella 44 cm, 15 cm superior patella 49, 20 cm superior patella 50 cm, patella 36.5 cm, 5 cm tibial tuberosity 35 cm, 10 cm tibial tuberosity 35 cm. And in therapy 6th obtained results 10 cm superior patella 46 cm, 15 cm superior patella 50 cm, 20 cm superior patella 53 cm, patella 35.5 cm, 5 cm tibial tuberosity 35 cm, 10 cm tibial tuberosity 35 cm and increase ability functional limbs lower with questionnaire (LEFS) 45% at baseline therapy to 41% at the end therapy. Intervention ultrasound and therapeutic physiotherapy exercise can reduce painful motion , increase LGS, increase strength muscle and mass muscle and improve ability functional limbs down in left jumpers knee condition.